2009
DOI: 10.1108/14635770910936522
|View full text |Cite
|
Sign up to set email alerts
|

Improving of the efficiency through benchmarking: a case of Ukrainian breweries

Abstract: Purpose -The purpose of this paper is to investigate the use of competitive and international performance benchmarking in order to estimate efficiency, determine key factors, find the internal and foreign benchmarks, and reveal the full reserves of inputs reduction and potential growth efficiency for brewing companies. Design/methodology/approach -Data envelopment analysis (DEA) and other tools of performance benchmarking are used to analyse the efficiency of brewing companies. Some key factors are examined fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…This set of inputs and output variables is well justified in previous studies, for example, for breweries (Goncharuk, 2009b) and sugar plants (Goncharuk, 2009a).…”
Section: Methodsmentioning
confidence: 73%
See 2 more Smart Citations
“…This set of inputs and output variables is well justified in previous studies, for example, for breweries (Goncharuk, 2009b) and sugar plants (Goncharuk, 2009a).…”
Section: Methodsmentioning
confidence: 73%
“…Among existing DEA models in the context of a given research, it is expedient to use the following: To estimate an efficiency score for each wine company, the common input-oriented model with a constant returns of scale (CRS) (Charnes et al , 1978) and input-oriented model with a variable returns of scale (VRS) (Banker et al , 1984) will be used. To estimate an influence of production scale on the winery efficiency and to define RTS for each winery, the parameter of scale efficiency will be defined on the following ratio: where TE CRS is technical efficiency score for CRS model and TE VRS is technical efficiency score for VRS model (Goncharuk, 2009b). To make full ranking of wine companies, the DEA model of super-efficiency, offered by Anderson and Petersen (1993), will be used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DEA models have also been applied to study the influence of endogenous and exogenous factors on liquor company efficiency. For example, Goncharuk (2009) analysed the efficiencies and explored the key factors affecting efficiency: scale, location, operations, and other internal and external factors: in 34 Ukrainian brewing companies and 20 foreign brewing companies, from which it was found that only one company in Ukraine was world-class and efficient. Li et al (2013) measured the Distribution Centre productivity using DEA to determine the relationships between the different influencing variables in 108 distribution centres of a large beverage company, finding that high productivity did not always guarantee a good earnings performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, beer is worldwide one of the most consumed beverages and the preference of 11-15 years old adolescents (Currie, 2004;WHO, 2014). On top of that beer consumption in Ukraine has tripled between [2002][2003][2004][2005][2006][2007][2008][2009] (Goncharuk, 2009). In Ukraine 9.3% of boys and 3.1% of girls of 11 years old drink alcohol weekly (Currie, 2004).…”
Section: The Influence Of Context: Family and Community In Ukrainementioning
confidence: 99%